Assessment criterion for indoor noise disturbance in the presence of low frequency sources. (1st December 2016) - Caniato, M.; Bettarello, F.; Schmid, C.; Fausti, P.
Abstract: Several studies have presented the effects of environmental noise in and around buildings and communities in which people live and work. In particular, the noise introduced into a building is mostly evaluated using the A weighted sound pressure level ( L Aeq ) as the only parameter to determine the perceived disturbance. Nevertheless, if noise is produced by activities or sources characterised by a low frequency contribution, the measurement of L Aeq underestimates the real disturbance, in particular during sleeping time. The international literature suggests methods to evaluate the low-frequency noise contribution to annoyance separately from the A weighted sound pressure level; almost all of the proposed methods are based on exceeding a threshold limit. This paper tests international criteria, by applying them in real-life indoor noise situations, and then analysing, comparing and contrasting results. Based on the result of the procedure above, a new criterion consisting of a single threshold is proposed, which simplifies the procedures in case of low-frequency components, but could be used for any situation.